IMPLEMENTASI MODEL EXPERIENTAL LEARNING DALAM PEMAHAMAN MATEMATIS MATERI PECAHAN SEDERHANA SISWA KELAS II A SD SUPRIYADI SEMARANG - Khusnul Himmah; Aryo Andri Nugroho; Ariani Nur Setyaningsih (Jurnal Binagogik, 2024)
This article is part of research on developing learning tools using a game-based experiential learningmodel. This research aims to describe the implementation of the experiential learning model inproviding students' mathematical understanding of simple fractions material for class II students. Thisexperiential learning learning model is created in a game called the fraction card game. The researchmethod used is qualitative with an emphasis on collecting data through observation, interviews anddocument analysis. The subjects of this research were class II A students at SD Supriyadi Semarang.The research results show that students can form their mathematical understanding of simple fractionmaterial through an experiential learning model during the learning process.